2017
DOI: 10.1111/jan.13490
|View full text |Cite
|
Sign up to set email alerts
|

Research recruitment: A marketing framework to improve sample representativeness in health research

Abstract: This framework challenges researchers to investigate the goals of the potential participants when designing a study's advertising and procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The analysis was conducted, as outlined by Gale, Heath, Cameron, Rashid, and Redwood (2013), using NVivo version 11.3.2.779 to organise the data into matrices and to link summaries in the matrices to the full transcripts. Initial codes were identified after a critical review of the literature (Howcutt et al 2017b). Further themes were added after familiarisation with the data through transcription, conducted by SJH and hearing/reading the data multiple times.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis was conducted, as outlined by Gale, Heath, Cameron, Rashid, and Redwood (2013), using NVivo version 11.3.2.779 to organise the data into matrices and to link summaries in the matrices to the full transcripts. Initial codes were identified after a critical review of the literature (Howcutt et al 2017b). Further themes were added after familiarisation with the data through transcription, conducted by SJH and hearing/reading the data multiple times.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a literature review of theories of research participation and trials of strategies to increase the recruitment of women to health research (Howcutt et al 2017b). Following this reading of evidence, the questions were designed to focus conversations around the following areas:…”
Section: Development Of the Topic Guidementioning
confidence: 99%
See 1 more Smart Citation
“…Howcutt and colleagues propose a marketing framework to improve recruitment [ 32 ]. Combined perspectives of marketing science and behavioral science focus on persuasion and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Friedman et al, 2015;L.M. Friedman et al, 2015;Fry et al, 2017;Davison et al, 2017;Bartlett et al, 2018;Howcutt et al, 2018). However, while several longitudinal studies have reported impacts of disasters on their participant cohorts (La Greca et al, 1996;Warheit et al, 1996;Norris et al, 2006;Proctor et al, 2007;McGonagle et al, 2008;Lankenau et al, 2010;Satherley et al, 2015;Byrd-Bredbenner et al, 2017), few have addressed specific recruitment, retention or attrition issues associated with these impacts and their potential effect on results.…”
Section: Introductionmentioning
confidence: 99%